Higher 3-year recurrence-free survival rate in patients with complete pathological remission following neoadjuvant chemotherapy plus immunotherapy for esophageal cancer: a two-center, propensity score matching study - Zhang, Hai; He, Haiquan; Feng, Qingyi; Wu, Bomeng; Chen, Ying; Zhang, Zhenyang; Zhou, Linrong; Li, Cui; Lin, Wanli; Lin, Jiangbo (Frontiers in Oncology, 2025)
BackgroundNeoadjuvant therapy is preferentially recommended for resectable locally advanced esophageal malignancies, with patients who achieve pathological complete response (PCR) anticipated to have longer survival rates. The aim of this study was to compare 3-year follow-up data for patients with esophageal malignancy who achieved PCR through neoadjuvant chemotherapy (nCRT) and to compare the findings with those of neoadjuvant immunotherapy plus chemotherapy (nICT).MethodsThis retrospective study included 85 patients with esophageal cancer who underwent surgical resection following nCRT (n=47) or nICT (n=38) between January 1, 2016 and January 1, 2020 at Fujian Medical University Union Hospital and Gaozhou People’s Hospital. Propensity score matching was used to match baseline data and reduce bias between the patient groups. Data during the neoadjuvant treatment and perioperative periods were compared, and follow-up was performed to evaluate differences in 3-year survival rate and recurrence-free survival.ResultsAfter propensity score matching, 28 nCRT patients and 38 nICT patients were included. During neoadjuvant therapy, the nCRT group had higher incidences of leukopenia and neutropenia than did the nICT group. No significant differences were observed in the incidences of hemoglobin decrease, platelet decrease, liver function damage, elevated serum creatinine, diarrhea, radioactive pneumonia or immunotherapy-related pneumonia, and esophageal perforation. The nCRT group had fewer lymph node dissections and lymph node stations. Postoperative lung infection (50.00%) was significantly higher in the nICT group than in the nCRT group (25.00%). The 3-year survival rates were 97.37% and 85.71% in the nICT and nCRT groups, respectively; the 3-year recurrence-free survival rate was significantly lower in the nCRT group (82.14%) than in the nICT group (97.37%, P=0.02).ConclusionsThese findings suggest that patients with esophageal cancer who achieve PCR after nICT treatment may have lower rates of disease recurrence.